Fabrication and characterization of low-loss Al/Si/Al parallel plate capacitors for superconducting quantum information applications - Anthony P. McFadden; Aranya Goswami; Tongyu Zhao; Teun van Schijndel; Trevyn F. Q. Larson; Sudhir Sahu; Stephen Gill; Florent Lecocq; Raymond Simmonds; Chris Palmstrøm (npj Quantum Information)
Abstract Increasing the density of superconducting circuits requires compact components, however, superconductor-based capacitors typically perform worse as dimensions are reduced due to loss at surfaces and interfaces. Here, parallel plate capacitors composed of aluminum-contacted, crystalline silicon fins are shown to be a promising technology for use in superconducting circuits by evaluating the performance of lumped element resonators and transmon qubits. High aspect ratio Si-fin capacitors having widths below 300 nm with an approximate total height of 3 μm are fabricated using anisotropic wet etching of Si(110) substrates followed by aluminum metallization. The single-crystal Si capacitors are incorporated in lumped element resonators and transmons by shunting them with lithographically patterned aluminum inductors and conventional A l/A l O x /A l Josephson junctions respectively. Microwave characterization of these devices suggests state-of-the-art performance for superconducting parallel plate capacitors with low power internal quality factor of lumped element resonators greater than 500 k and qubit T 1 times greater than 25 μs. These results suggest that Si-Fins are a promising technology for applications that require low-loss, compact, superconductor-based capacitors with minimal stray capacitance.